Analyzing The Effectiveness Of E-Commerce Marketplace Coupon In The Culinary Industry: A Case Study Of Dago Restaurant Jakarta (The Indonesian Journal of Business Administration, 2020)
New culinary industry opportunities always arise created by entrepreneurs. With the times, the culture of Indonesian society today has also changed. Indonesian people are easy to accept and adapt to various types of food. Such potential is the target for foreign parties who want to invest in Indonesia. Many foreign restaurants have sprung up in Indonesia, one of which is DaGo Restaurant Jakarta. In introducing the restaurant, DaGo Restaurant Jakarta does not want to be out of date so DaGo Restaurant Jakarta uses the help of technology by using e-commerce marketplace. DaGo Restaurant Jakarta collaborates with an e-commerce marketplace in Indonesia named LaKupon. However, in its implementation the collaboration between DaGo Restaurant Jakarta and LaKupon did not go well. The function of DaGo Restaurant Jakarta using LaKupon is to increase visitor traffic, but in reality DaGo Restaurant Jakarta actually loses its revenue potential because the use of vouchers from LaKupon itself does not reach the target. Therefore DaGo Restaurant Jakarta must make a decision on how to increase their visitor traffic. The problem of choosing a new and appropriate e-commerce marketplace for DaGo Restaurant Jakarta is analyzed using the Analytic Hierarchy Process (AHP). As a result of AHP, Fave is the best choice as a new e-commerce marketplace to increase customer traffic for DaGo Restaurant Jakarta.